Hubungan Tingkat Stres dengan Kecenderungan Merokok Pada Remaja Laki-Laki di SMK Negeri 3 Palembang Tahun 2025: Penelitian - Riko Sandra Putra; Trie Septiana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Smoking among adolescents, especially males, is often triggered by high levels of stress and is perceived as a coping mechanism to deal with pressure. This study aims to determine the relationship between stress levels and the tendency to smoke among male adolescents at SMK Negeri 3 Palembang in 2025. This research employed a quantitative method with a cross-sectional approach. The sample consisted of 61 male adolescents selected using a total sampling technique. The instrument used in this study was the Perceived Stress Scale (Sheldon Cohen, 1983), modified by Yolanda Faradila (2020). The results showed that most participants experienced moderate stress (49.2%), followed by mild stress (41.0%), and severe stress (9.8%). Similarly, the tendency to smoke was highest in the moderate category (49.2%), followed by mild (41.0%), and severe (9.8%). The findings revealed a significant relationship between stress levels and smoking tendencies among male adolescents at SMK Negeri 3 Palembang, with a p-value of 0.000 (< 0.05). This indicates that the higher the stress level experienced by adolescents, the greater their tendency to smoke. In this context, smoking acts as a form of negative coping mechanism used by adolescents to handle the stress they face.